(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
According to estimation, India currently has 6.7% over 65 years of age, which is expected to increase to 20% by the year 2050. As growing old is a part of the life cycle, the effect of time is bound to happen and is unavoidable. The Kalajajara is a Swabhavika vyadhi, wherein, it is clearly mentioned that Swabhava balapravritta vyadhis being Yapya, can be managed through Bhojana, Paana, and Rasayana. Vriddadaru Rasayana is one such Rasayana mentioned in Gadanigraha especially for the elderly to promote healthy ageing and helping to prevent old age problems. Aims and objectives: To assess the effect of Vriddadaru Rasayana in improving the general body health and quality of life in the apparently healthy elderly subjects. Methodology– A Randomized double blind clinical study where 20 healthy elderly subjects were administered with Vriddadaru Rasayana for a period of 12 weeks. Observations and Results- Vriddadaru rasayana showed improvement in Ayurvedic parameters like Twakparushata, Slataasti, Slata sandhi, Utasahahani and Parakramahani but when compared with regard to objective parameters Vriddadaru rasayana showed significant values in DHEAS levels and 6MWT. Conclusion: Vriddadaru does Vatashamana, balancing the Doshas, increasing the Utsaha and Parakrama and helps in improving the Agni thus helping in Dhatuposhana in the elderly.